MDL-800, the SIRT6 Activator, Suppresses Inflammation via the NF-κB Pathway and Promotes Angiogenesis to Accelerate Cutaneous Wound Healing in Mice. (27th April 2022) - Jiang, Xiaoqi; Yao, Zhe; Wang, Kangyan; Lou, Lihua; Xue, Kaikai; Chen, Jinghao; Zhang, Guojian; Zhang, Yu; Du, Jiqing; Lin, Cai; Xiao, Jian
Abstract : Sirtuin 6 (SIRT6) is an NAD + -dependent deacetylase belonging to the sirtuin family. It has been shown to participate in wound healing and some inflammation-related disorders. However, the effect of MDL-800, a highly efficient and selective SIRT6 activator, on wound healing and inflammation has not been reported. Therefore, this study investigated whether MDL-800 confers anti-inflammatory effects and promotes wound healing and uncovered the molecular mechanisms involved. This was achieved using mouse models of full-thickness wounds. Results showed that MDL-800 significantly downregulated inflammation by attenuating the release of inflammatory mediators and improved collagen deposition and neovascularization of wounds, thereby accelerating cutaneous wound healing. Furthermore, MDL-800 significantly downregulated expression levels of TNF- α and IL-6 in the dorsal skin tissue of mice via the NF- κ B pathway. These results demonstrated that MDL-800 exerted anti-inflammatory and prohealing effects, indicating that the SIRT6/NF- κ B/I κ B signaling pathway may play an important role in wound healing.